ANALISIS FAKTOR MEMENGARUHI PENINGKATAN PENDAPATAN PETERNAK AYAM DESA TOLBUK BANGKALAN - Jannah, Hilyatul; Tarman, Manah (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the factors influencing the increase in income of chicken farmers in Tolbuk Village, Klampis District, Bangkalan Regency. The variables examined include business capital, production costs, livestock technology, access to information, and social factors. This research is based on the existence of income disparities among farmers due to differences in resources, management, and local conditions. A qualitative approach with a case study method was employed. Data were collected through interviews, observation, and documentation involving five informants consisting of farm owners and workers. Data analysis was carried out through data reduction, data display, and conclusion drawing to provide a comprehensive understanding of the research problem. The findings show that business capital significantly affects the scale and continuity of farming activities. Production costs, especially feed costs, are the main factor influencing income levels. Livestock technology contributes to improving efficiency, although its application is still limited. Access to information helps farmers make better decisions regarding market prices and selling time. Social factors, including family support and cooperation among farmers, also play an important role in supporting business success. In conclusion, the increase in farmers’ income is determined by the synergy of capital, cost efficiency, technology, information access, and social support.